2019
DOI: 10.1002/hep.30365
|View full text |Cite
|
Sign up to set email alerts
|

Peribiliary Glands Are Key in Regeneration of the Human Biliary Epithelium After Severe Bile Duct Injury

Abstract: Peribiliary glands (PBG) are a source of stem/progenitor cells organized in a cellular network encircling large bile ducts. Severe cholangiopathy with loss of luminal biliary epithelium has been proposed to activate PBG, resulting in cell proliferation and differentiation to restore biliary epithelial integrity. However, formal evidence for this concept in human livers is lacking. We therefore developed an ex vivo model using precision‐cut slices of extrahepatic human bile ducts obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 36 publications
5
53
1
Order By: Relevance
“…Taken together, our data indicate an active contribution by SOX9 + PBG cells in the restoration of SE after injury and their capability to differentiate into mature cholangiocytes. Our findings are in keeping with the evidence that the regeneration of ischemic injured SE is ensured by BTSC activation in a human ex vivo model …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Taken together, our data indicate an active contribution by SOX9 + PBG cells in the restoration of SE after injury and their capability to differentiate into mature cholangiocytes. Our findings are in keeping with the evidence that the regeneration of ischemic injured SE is ensured by BTSC activation in a human ex vivo model …”
Section: Discussionsupporting
confidence: 91%
“…PBGs can produce Notch ligands themselves, thus suggesting an autocrine effect and a further paracrine effect on neighboring (myo‐)fibroblasts. Interestingly, previous evidence indicated that, in human biliary disease, PBGs can secrete vascular endothelial growth factors (VEGFs), influencing the modification of peribiliary vascular plexus in PSC and hypoxic conditions . Taken together with previous studies, our results indicate that the activation of PBG niche represents a consequence of toxic or inflammatory biliary damage (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The PBGs/PPGs secrete mucus and immunoglobulin, thus contributing to the protection of the apical surface of the bile duct epithelia from bile salt toxicity (DiPaola et al, 2013;Hopwood et al, 1988;Sugiura and Nakanuma, 1989). PBGs also contain epithelial cells expressing several biliary and hepatic stem cell markers (including Sox9, Sox17, Pdx1 and Lgr5), and it has therefore been suggested that they may be the reservoir of epithelial stem/progenitor cells in the biliary tract (Furuyama et al, 2011;Cardinale et al, 2012;Carpino et al, 2012;DiPaola et al, 2013;Lanzoni et al, 2016;Matsui et al, 2018;de Jong et al, 2018de Jong et al, , 2019. Therefore, it is possible that the metaplastic PBG/PPG-like glands may serve as a positive response to regenerate the epithelial structure in the BA gallbladders following stress/inflammation during late fetal and perinatal periods.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these findings are confirmed by single-cell transcriptomic analysis in human, with the identification of an EpCAM pos / TROP2 int / MUC6 high progenitor compartment with prominent stem cell features ( 9 ). Moreover, the contribution of PBG cells in the regeneration of mature biliary epithelium has been demonstrated in experimental conditions and by an ex vivo human model of biliary regeneration, which have disclosed that PBG cells can repopulate the surface epithelium of bile ducts by proliferation and differentiation into mature cholangiocytes ( 25 , 28 , 29 ).…”
Section: The Heterogeneity Of Epcam Pos Cell Populmentioning
confidence: 99%